Postural Improvement Through Progressive Strengthening of Serratus Anterior and Rhomboid Muscle in Forward Head Posture Cases - Ika Guslanda Bustam; Yudiansyah (Universitas Negeri Semarang, 2025)
Forward Head Posture (FHP) is a prevalent musculoskeletal disorder, especially among university students engaged in prolonged sedentary activities. Weakness in scapular stabilizing muscles such as the serratus anterior and rhomboids contributes significantly to postural misalignment and associated pain. This study aimed to investigate the effectiveness of progressive strengthening exercises targeting the serratus anterior and rhomboid muscles in improving craniovertebral angle, reducing neck pain, and enhancing functional outcomes in final-year university students with FHP. A quasi-experimental pre-test and post-test design was employed involving 67 final-year students. Participants were divided into an intervention group (n=33) and a control group (n=34). The intervention group underwent a progressive strengthening program 3 sessions per week over 4 weeks, while the control group received no physiotherapy. Outcome measures included craniovertebral angle (CVA), Numeric Rating Scale (NRS) for pain, and the Neck Disability Index (NDI). The intervention group demonstrated a significant improvement in CVA increased from 42.1° ± 2.5° to 49.3° ± 2.8° (p < 0.001), compared to a non-significant change in the control group 42.5° ± 2.3° to 43.1° ± 2.6° (p < 0.001). NRS decreased from 5.6 ± 1.2 to 2.1 ± 0.9 (p = 0.000), and NDI scores dropped from 32.4 ± 4.7 to 15.3 ± 3.9 (p = 0.000). The control group showed no significant changes in any measure. Progressive strengthening of the serratus anterior and rhomboid muscles is effective in correcting forward head posture, alleviating pain, and improving cervical function. These findings support the integration of targeted postural exercises into student wellness and physiotherapy programs.